Makamsız : individualization of traditional music on the eve of Kemalist Turkey - Greve, Martin (2017)
The book describes the confusing, contradictory and individualized musicscape in Turkey around the turn of the twenty-first century, including its prehistory throughout the twentieth century and sometimes beyond. Its focus lies on the recent tendency towards a disintegration of musical traditions into internationalism and multiple musical hybrids which might be described as a process of individualization.